1988
DOI: 10.3109/00365528809093870
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the Stomach and Its Heredity in Young Patients

Abstract: The clinical and histopathologic characteristics of gastric carcinoma in young patients (less than 40 years old) were studied retrospectively. The carcinoma was of the diffuse type in 94% of the young patients, and typical features were poor prognosis, an equal sex ratio, and a strong association with blood group A. The family histories of the young patients were studied. There was a highly significant (p less than 0.001) overrepresentation of gastric cancer in the parents of the index cases. In four instances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
1
5

Year Published

1991
1991
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 22 publications
3
16
1
5
Order By: Relevance
“…This may indicate differences in exposure to risk factors and differences in prognosis. Diffuse type is known to occur more in younger individuals and to be associated with poor prognosis [20,21]. Such type-age correlation was not evident in our patient population.…”
Section: Discussionmentioning
confidence: 39%
“…This may indicate differences in exposure to risk factors and differences in prognosis. Diffuse type is known to occur more in younger individuals and to be associated with poor prognosis [20,21]. Such type-age correlation was not evident in our patient population.…”
Section: Discussionmentioning
confidence: 39%
“…It has also been reported that patients with diffuse gastric carcinoma are younger than those with the intestinal-type (Lauren, 1965;Noda et al, 1980;Ribeiro et al, 1981;Hanai et al, 1982;Mecklin et al, 1988). Two studies are concordant that this difference is in the order of 7-8 years (Lauren, 1965;Ribeiro et al, 1981).…”
supporting
confidence: 53%
“…Accordingly, it is recommended that resections should be more extensive in patients with this tumour than in patients with the intestinaltype tumour (Gall & Hermanek 1985, Heberer et al, 1988. It is well documented that the prognosis for the diffuse carcinoma is poorer than for the intestinal-type carcinoma (Lauren, 1965;Stemmermann & Brown, 1974;Ribeiro et al, 1981; Hermanek, 1986;Viste et al, 1986).It has also been reported that patients with diffuse gastric carcinoma are younger than those with the intestinal-type (Lauren, 1965;Noda et al, 1980;Ribeiro et al, 1981;Hanai et al, 1982;Mecklin et al, 1988). Two studies are concordant that this difference is in the order of 7-8 years (Lauren, 1965;Ribeiro et al, 1981).…”
mentioning
confidence: 99%
“…Previous reports on various populations have suggested that a family history of gastric cancer (GC) is an important risk for GC [1, 2, 3, 4, 5]. However, the clinicopathological characteristics of GC with a positive family history of site- specific GC have not been well discussed.…”
Section: Introductionmentioning
confidence: 98%